Assessment of MultiLocus Sequence Analysis As a Valuable Tool for the Classification of the Genus Salinivibrio - López-Hermoso, Clara; de la Haba, Rafael R.; Sánchez-Porro, Cristina; Papke, R. Thane; Ventosa, Antonio (Frontiers in Microbiology, 2017)
The genus Salinivibrio includes obligatory halophilic bacteria and is commonly isolated from hypersaline habitats and salted food products. They grow optimally between 7.5-10 % salts and are facultative anaerobes. Currently, this genus comprises four species, one of them, Salinivibrio costicola, with three subspecies. In this study we isolated and characterized an additional 70 strains from solar salterns located in different locations. Comparative 16S rRNA gene sequence analysis identified these strains as belonging to the genus Salinivibrio but could not differentiate strains into species-like groups. To achieve finer phylogenetic resolution, we carried out a MultiLocus Sequence Analysis (MLSA) of the new isolates and the type strains of the species of Salinivibrio based on the individual as well as concatenated sequences of four housekeeping genes: gyrB, recA, rpoA and rpoD. The strains formed four clearly differentiated species-like clusters called phylogroups. All of the known type and subspecies strains were associated with one of these clusters except S. sharmensis. One phylogroup had no previously described species coupled to it. Further DNA-DNA hybridization (DDH) experiments with selected representative strains from these phylogroups permitted us to validate the MLSA study, correlating the species level defined by the DDH (70 %) with a 97 % cut-off for the concatenated MLSA gene sequences. Based on these criteria, the novel strains forming phylogroup 1 could constitute a new species while strains constructing the other three phylogroups are members of previously recognized Salinivibrio species. S. costicola subsp. vallismortis co-occurs with S. proteolyticus in phylogroup 4, and separately from other S. costicola strains, indicating its need for reclassification. On the other hand, genome fingerprinting analysis showed that the environmental strains do not form clonal populations and did not cluster according to their site of cultivation. In future studies regarding the classification and identification of new Salinivibrio strains we recommend the following strategy: i) initial partial sequencing of the 16S rRNA gene for genus-level identification; ii) sequencing and concatenation of the four before mentioned housekeeping genes for species-level discrimination; iii) DDH experiments, only required when the concatenated MLSA similarity values among a new isolate and other Salinivibrio strains are above the